ENGLISH FOR SPECIFIC PURPOSES IN AVIATION: A NEEDS-BASED APPROACH FOR AIR TRAFFIC CONTROLLERS AND MAINTENANCE TECHNICIANS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Effective English communication is essential for ensuring safety, operational effectiveness, and regulatory compliance in international aviation. The design and execution of an English for Specific Purposes (ESP) course for B1-level air traffic controllers and aviation maintenance workers are described in this paper. Based on frameworks developed by Woodrow (2018), Bosher (2008), and Swales (1988), the course incorporates intercultural communication techniques, real-world simulations, and Problem-Based Learning (PBL). To determine the learners' unique language and professional demands, a mixed-methods needs analysis was carried out utilising surveys and interviews. The importance of ESP in high-stakes, multicultural aviation situations is highlighted in this paper, which also covers the course's learner profile, instructional design, and assessment techniques.